CSIG-09. ASSESSMENT OF TUMOR TREATING FIELDS (TTFields) COMBINED WITH TRICHOSTATIN A (TSA) IN PATIENT-DERIVED GLIOBLASTOMA (GBM) CELLS. (12th November 2021) - Ma, Manxiu; Michelhaugh, Sharon; Mittal, Sandeep
Abstract: BACKGROUND: TTFields therapy is a non-invasive biophysical approach for GBM patient treatment. TTFields produce an anti-mitotic effect by destabilizing microtubule polymerization and interrupting cell division. However, epigenetic modifications that may be induced by TTFields remain unknown. To address this, TTFields were applied to patient-derived GBM cells ± the histone deacetylase (HDAC) inhibitor trichostatin A (TSA) and cellular proliferation was assessed. HDAC activity was also measured after TTFields application. METHODS: GBM cells were isolated from a newly-diagnosed patient tumor (IDH-WT, unmethylated MGMT promoter). Cells were grown in DMEM/F12 media with 10% FBS and gentamicin. Cells were plated on plastic coverslips (1×10 4 cells/coverslip) and incubated overnight. TTFields were applied at 200 kHz (field intensity of 1.6 V/cm) for 6 days. For the last 2 days of TTFields, cells were incubated with DMSO or 250 nM TSA. Cells were harvested and counted to assess proliferation (n=4-5/group). To determine if TTFields have a direct effect on HDAC activity, TTFields were applied as described and nuclei were extracted. Nuclear HDAC activity was measured using a commercial kit (n=2-3/group). Cell counts were compared with one-way ANOVA and Tukey multiple comparisons with p< 0.05 considered significant. RESULTS: Cell counts for the DMSO control group, TSA only, TTFields only, and the combination were: 643, 400 ± 111, 384, 233, 800 ± 144, 200, 90, 775 ± 45, 209, and 41, 520 ± 36, 168, respectively (mean ± SD; ANOVA p < 0.0001). There was no statistical difference between the TTFields only and TSA only or TTFields + TSA groups, with all other comparisons statistically significant. For the HDAC activity measurements, control nuclei were 1068 ± 135 pmol/min/mg and TTFields-treated nuclei were 1301 ± 313.6 pmol/min/mg and were not statistically different. CONCLUSIONS: The addition of TSA to TTFields did not alter cellular proliferation more than TTFields alone and TTFields did not alter HDAC activity in these GBM cells.